Status of Mangrove Wetlands of Nellore and Prakasam Districts, Andhra Pradesh, India - Krishna Rao, N. S. R. (Indian Forester, 2016)
A comprehensive survey along the 295 Km. coastline of Nellore and Prakasam districts of Andhra Pradesh was conducted to assess the present status of mangrove wetlands and their diversity. Total extent of mangrove cover in these two districts is 2541 ha occurring in 30 different locations of which 23 are in Nellore district and seven are in Prakasam district. Twelve true mangroves from six families and nineteen mangrove associates from eleven families were recorded in the present study. Avicennia marina, Rhizophora mucronata, Excoecaria agallocha and Aegiceras corniculatum are the dominant mangroves in the major wetlands of the two districts. Kandelia candel is a new record for the state while Sonneratia apetala is confmed to Ponnapudi wetland in the tskapalli lagoon of Nellore district. The mangrove wetland is under threat like other parts of the world.